EVALUATING STRATEGIC LEADERSHIP EFFECTIVENESS IN GOVERNMENT INSTITUTIONS : A SYSTEMATIC LITERATURE REVIEW - Semail, Endo; Abdul Halim, Busari; Dayang Kartini, Abang Ibrahim (Global Academic Excellence (M) Sdn Bhd (GAE), 2024)
This systematic literature review examines the effectiveness of strategic leadership within government institutions. Strategic leadership, a critical component in public sector management, is essential for navigating complex policy environments and achieving organizational goals. The study addresses the problem of inconsistent outcomes in government leadership effectiveness, which can hinder policy implementation and public trust. To achieve this, we conducted an extensive search of scholarly articles from reputable databases such as Scopus and Web of Science, focusing on studies published between 2020 and 2024. The flow of study based on PRISMA framework. The database found (n=20) final primary data was analysed. The finding was divided into three themes which is (1) Strategic Management in Public and Private Sectors, (2) Economic Development and Regional Planningand (3) Organizational Performance and Innovation. The review concludes that while strategic leadership is essentialfor governmental success, continuous adaptation and training are required to overcome inherent obstacles. Future research should focus on developing innovative leadership models tailored to the dynamic nature of the public sector